ANIMPROVED TECHNIQUE FOR HUMAN FACE RECOGNITION USING IMAGE PROCESSING - YogeshB. Sanap,; Dr. Anilkumar N. Holambe, (International Journal of Innovations in Engineering Research and Technology, 2021)
Facerecognition is a computer application technique for automatically identifying or verifying a person from a digital image or avideo framesource. To do this is by comparing selected facial features from the digital image and a face dataset. It is basically used in security systems and can be compared to other biometrics such as fingerprint recognition or eye, iris recognition systems.The main limitation of the current face recognition system is that they only detect straightfaces looking at the camera. Separate versions of the system could be trained for each head orientation, and the results can be combined using arbitration methods similar to those presented here. In earlierwork, the face position must be center-light position; any lighting effect will affect the system. Similarly the eyes of person must be open and without glass. I